Interkoneksi Nilai-Nilai Huma Betang Kalimantan Tengah dengan Pancasila - AS Pelu, Ibnu Elmi; Tarantang, Jefry (Jurnal Studi Agama dan Masyarakat, 2018)
Huma betang  is a typical traditional house inhabited by Dayak people. The life intertwined from the residents of the Betang Huma is safe, peaceful and warmly in  differences. This research is a qualitative research with an empirical and normative approach focusing on the philosophy of Huma betang  and its relationship to Pancasila. This study reveals that Pancasila can be seen from the foundation of life of Central Kalimantan people, namely Garing Hatungku Tungket Langit, isen mulang, Hupungkal Lingu Nalatai Hapangajan Karendem Malempang, dan Belom Bahadat. If it is seen from the relationships and its interrelations, there is an interconnection of the Huma betang  values of the Central Kalimantan Dayak people with the Pancasila philosophy  with the spirit of togetherness in difference of Unity in Diversity in the life of the nation and state.